Fast and high-affinity binding of B-lymphotropic papovavirus to human B-lymphoma cell lines. - Herrmann, M (1995)
Binding of B-lymphotropic papovavirus (LPV) to host cells differing in susceptibility to viral infection was determined by a newly established, direct, nonradioactive virus binding assay, which allows quantitative description of the binding characteristics by receptor saturation and Scatchard analysis. LPV binding to the highly susceptible human B-lymphoma cell line BJA-B K88 is specific, saturable, and noncooperative. Binding occurs very fast, with an association rate constant (k1) of 6.7 x 10(7) M-1s-1, and is of high affinity, with a dissociation constant (Kd) of 2.9 x 10(-12) M; and the virus-receptor complex is stable, with a half life of 70 min. The binding affinities of receptors on four other highly, moderately, or weakly susceptible human B-lymphoma cell lines were similar, with up to twofold variation around a mean Kd value of 3 x 10(-12) M, suggesting the presence of the same LPV receptor on all of these cell lines. This view is further supported by the finding that in all cases a terminal sialic acid is necessary for LPV binding. Tunicamycin has been shown to drastically induce LPV susceptibility and LPV binding in weakly and moderately susceptible B-lymphoma cell lines (O.T. Keppler, M. Herrmann, M. Oppenländer, W. Meschede, and M. Pawlita, J. Virol. 68:6933-6939, 1994). The hypothesis that the constitutively expressed and tunicamycin-induced LPV receptors are identical is strengthened by our finding that both receptor types displayed the same high affinity. LPV susceptibility of different B-lymphoma cell lines was correlated with receptor number but not with receptor affinity. The numbers of receptors per cell on highly and moderately susceptible cell lines ranged from 2,000 to 400 and were directly proportional to LPV susceptibility. This indicates that the number of high-affinity receptors per cell is a key regulating factor for the LPV host range.